The Influence of Corporate Image, Satisfaction of Trust and Loyalty of Plasma Farmer in Palm Oil Mill Sei Galuh PTPN V Riau - Hotmatua Hotmatua; Zulkarnain Zulkarnain; Marnis Marnis (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2018)
This study was aimed to analyze the influence of corporate image and satisfaction to trust. To analyze the influence of corporate image and satisfaction to loyalty and influence of farmer's confidence to farmer loyalty at palm oil mill Sei Galuh.The population of this research is 4.000 farmers. The sample size that will be used is 364 people. Data used in this research are primary data and secondary data. Data collection methods used by the authors in this study are by using Questionnaire. Data analysis method used is descriptive and quantitative. Descriptive is used to provide an overview of the data. Quantitative, i.e. analysis by collecting, categorizing and tabulating data, using the WarpPLS approach. Data analysis using WarpPLS approach.WarpPLS is an alternative approach that shifts from a Covariant-based SEM approach to variance-based.The results of this study show the image of the company affects the trust. These results prove that the better the image of the company then the confidence of farmers to the company will increase. Satisfaction affects trust. This proves that the better the satisfaction of farmers, the farmer's confidence in the company will increase. Corporate image affects loyalty. These results prove that the better the image of the company the higher the loyalty of farmers to the company. Satisfaction affects loyalty. This proves that the better the satisfaction of farmers, the loyalty of farmers to the company will increase. And Trust affects the loyalty of farmers. These results prove that the higher the confidence of farmers to the company, the higher the level of loyalty of farmers to the company.